Daily exposure to a touchscreen-paradigm and associated food restriction evokes an increase in adrenocortical and neural activity in mice - Mallien, Anne Stephanie; Inta, Dragos; Vollmayr, Barbara; Gass, Peter (Hormones and behavior, 2016)
The translational assessment of mechanisms underlying cognitive functions using touchscreen-based approaches for rodents is growing in popularity. In these paradigms, daily training is usually accompanied by extended food restriction to maintain animals' motivation to respond for rewards. Here, we show a transient elevation in stress hormone levels due to food restriction and touchscreen training, with subsequent adaptation effects, in fecal corticosterone metabolite concentrations, indicating effective coping in response to physical and psychological stressors. Corticosterone concentrations of experienced but training-deprived mice revealed a potential anticipation of task exposure, indicating a possible temporary environmental enrichment-like effect caused by cognitive challenge. Furthermore, the analyses of immediate early gene (IEG) immunoreactivity in the hippocampus revealed alterations in Arc, c-Fos and zif268 expression immediately following training. In addition, BDNF expression was altered as a function of satiation state during food restriction. These findings suggest that standard protocols for touchscreen-based training induce changes in hippocampal neuronal activity related to satiation and learning that should be considered when using this paradigm.